Acute Sciatic Neuritis following Lumbar Laminectomy - Foad Elahi; Patrick Hitchon; Chandan G. Reddy (Case Reports in Medicine)
It is commonly accepted that the common cause of acute/chronic pain in the distribution of the lumbosacral nerve roots is the herniation of a lumbar intervertebral disc, unless proven otherwise. The surgical treatment of lumbar disc herniation is successful in radicular pain and prevents or limits neurological damage in the majority of patients. Recurrence of sciatica after a successful disc surgery can be due to many possible etiologies. In the clinical setting we believe that the term sciatica might be associated with inflammation. We report a case of acute sciatic neuritis presented with significant persistent pain shortly after a successful disc surgery. The patient is a 59-year-old female with complaint of newly onset sciatica after complete pain resolution following a successful lumbar laminectomy for acute disc extrusion. In order to manage the patient’s newly onset pain, the patient had multiple pain management visits which provided minimum relief. Persistent sciatica and consistent physical examination findings urged us to perform a pelvic MRI to visualize suspected pathology, which revealed right side sciatic neuritis. She responded to the electrical neuromodulation. Review of the literature on sciatic neuritis shows this is the first case report of sciatic neuritis subsequent to lumbar laminectomy.